Personnel Information System at PT Tri Canis Aurum - Ferdiansyah Ferdiansyah; Steven Saputra; Mulyati Mulyati (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
A personnel management information system is a systematic procedure to collect, store, retain, retrieve, and validate data needed by an organization regarding human resources, personnel activities, characteristics of organizational units. PT Tri Canis Aurum is a private company engaged in acacia tree nursery services. In its business process, PT Tri Canis Aurum is still experiencing obstacles, namely the rectification process, managing employee data, calculating salaries, monitoring attendance, monitoring violations, applying for permits/leave, resigning, and assessing employee performance. The purpose of this research is to build a website-based personnel information system at PT Tri Canis Aurum to solve solutions to problems faced with employment. The methodology used is the iteration method, the problem analysis used is PIECES. At the design, the stage used Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). System development using Visual Studio Code and MySQL as the database. The results of the development of an employee information system at PT Tri Canis Aurum can help simplify the employee recruitment process, file employee data more effectively and efficiently, facilitate the attendance monitoring process, communicate between field supervisors and directors more effectively, more accurately calculate salaries and monitor violations